2005
DOI: 10.1159/000087923
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ghrelin in Anorexia, Bulimia, and Binge-Eating Disorder: Relations with Eating Patterns and Circulating Concentrations of Cortisol and Thyroid Hormones

Abstract: The present study was designed to investigate the relations between plasma ghrelin concentrations, eating patterns, and circulating concentrations of cortisol and thyroid hormones in women with anorexia nervosa, bulimia nervosa, and binge-eating disorder. The patterns of disordered eating behavior were assessed using the Eating Attitudes Test (EAT-26) and the Bulimia Test-Revised (BULIT-R). In women with eating disorders, but not in healthy control women, plasma ghrelin concentrations were negatively correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 69 publications
2
36
0
2
Order By: Relevance
“…Ghrelin levels in this patient group have been reported negatively correlated to BMI [103][104][105] and other nutritional parameters, such as percent body fat [105]. A relationship between plasma ghrelin levels and habitual binge-eating and purging seems difficult to be established.…”
Section: Ghrelin and Eating Disordersmentioning
confidence: 71%
See 1 more Smart Citation
“…Ghrelin levels in this patient group have been reported negatively correlated to BMI [103][104][105] and other nutritional parameters, such as percent body fat [105]. A relationship between plasma ghrelin levels and habitual binge-eating and purging seems difficult to be established.…”
Section: Ghrelin and Eating Disordersmentioning
confidence: 71%
“…In addition, both BN-P and AN-BP subjects have shown significant correlation among plasma ghrelin values, frequencies of binge-purge cycles and serum amylase values [105]. On the other hand, in a recent report, women with binge-eating and purging behaviour had lower ghrelin levels than women with AN-R [104]. Either ghrelin levels are influenced by habitual binge/puging or ghrelin concentrations simply reflect the nutritional status and energy imbalance regarded in these forms of eating disorders.…”
Section: Ghrelin and Eating Disordersmentioning
confidence: 92%
“…Очень вероятно, что НБ и МО (а точнее -BE-синдром, ведущий к МО) имеют одинаковую природу, которая до сих пор остается неяс-ной. Высказывались предположения о том, что наруше-ния в возникновении чувства насыщения во время еды объясняются нарушением моторики верхних отделов желудочно-кишечного тракта, секреции холецистоки-нина, высоким уровнем грелина и инсулина [24,34].…”
Section: Discussionunclassified
“…Patients with BED tend to show a decrease in ghrelin when fasting 53,63,68 and a lower postprandial decline compared to the obese control group 68 . This decrease in ghrelin does not seem to reduce the propensity to gain weight in BED patients.…”
Section: Ghrelin In Edsmentioning
confidence: 91%
“…The three groups experienced a decrease in their plasma levels of ghrelin after treatment, but patients with AN-P still kept the plasma levels of ghrelin higher than the control group at the end of rehabilitation 62 . In 2005 Troisi et al, found higher levels of ghrelin during fasting in AN-R patients when compared to the AN-P patients 63 . However, the Troisi group compared data between patients with AN-P and BN, which probably had a higher BMI, which may explain the difference between the results of the two studies.…”
Section: Ghrelin and The Regulation Of Appetitementioning
confidence: 96%